User Readiness Measurement of Campus Shuttle Mobile App “My Tuc-Tuc” Using TRI Model - Reza Reynaldi Tarigan; Rahmat Yasirandi; Hilal H. Nuha (My University, 2023)
The rapid development of application-based transportation services has brought about the emergence of various platforms, including “My Tuc-Tuc,” a specific transportation service developed by Telkom University. However, the operation of “My Tuc-Tuc” has faced several challenges, particularly concerning user experiences, especially among drivers. Therefore, this study aims to assess the technology readiness of “My Tuc-Tuc” users, focusing on their readiness across four personality traits: optimism, innovativeness, anxiety, and insecurity. These traits encompass both positive and negative perspectives. The study employed the Technology Readiness Index (TRI) methodology, a well-established framework for evaluating users' readiness to adopt and utilize technology. The selection of participants involved utilizing the Slovin formula, resulting in a sample size of 12 “My Tuc-Tuc” users who also served as TelU Car drivers. Rigorous validity and reliability tests were conducted to ensure the accuracy and consistency of the collected data. Subsequently, the TRI scores were calculated based on the participants' responses. The findings of the study revealed a TRI score of 3.9098, indicating that “My Tuc-Tuc” users fall within the high technology readiness category according to the TRI classification. This suggests that these users are well-prepared and receptive to the utilization of the “My Tuc-Tuc” application-based transportation service. The results provide valuable insights for Telkom University and the “My Tuc-Tuc” team, enabling them to identify and address the challenges faced by users and develop appropriate strategies to enhance the overall user experience and service quality. This study contributes to the existing literature on technology readiness and offers practical implications for the further development and improvement of “My Tuc-Tuc” as a reliable and user-friendly transportation service. Future research endeavors could explore additional dimensions of technology readiness and examine factors influencing user satisfaction and loyalty, thereby providing a more comprehensive understanding of user behaviors and preferences in the context of application-based transportation services.
Keywords: Technology Adoption and User Behaviour; Innovation in Digital Healthcare Systems; Technology and Data Analysis